(untitled) - Mader, Sylvia S. (New York, 2007)
Biology is a comprehensive introductory biology textbook for non-majors or mixed-majors courses that covers biology in a traditional order from the structure and function of the cell to the organization of the biosphere. The book, which centers on the evolution and diversity of organisms, is appropriate for a one- or two-semester course. It's no wonder that Sylvia Mader's Biology continues to be a text that's appreciated as much by instructors as it is by the students who use it. The ninth edition is the epitome of Mader's expertise: Its concise, precise writing uses an economy of words to present the material as succinctly and clearly as possible, thereby enabling students -- even non-majors -- to understand the concepts without necessarily asking the instructor to explain further.
Keywords: Biology